Management of Acute Complicated Mastoiditis: A Systematic Review and Meta-analysis. Issue 4 (16th February 2022) - Kaufmann, Matthew R.; Shetty, Kunal; Camilon, P. Ryan; Shetty, Anisha; Levi, Jessica R.; Devaiah, Anand K.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The objective of our study was to evaluate the efficacy of treatment options for the most frequently reported complications of acute mastoiditis in the English literature. PubMed, EMBASE, and The Cochrane Library were searched from database inception through March 29, 2019. Methods: Two independent reviewers (M.R.K., K.S.) evaluated search results for study inclusion. References cited in publications meeting inclusion criteria were reviewed. Twenty-three included studies were published from 1998 through 2018. Treatment efficacy was determined by comparing the change in number of complication subtypes in each treatment subgroup (medical, conservative, or surgical) from admission to discharge (range: 5–30 days) or postdischarge follow-up (range: 1–27.5 months) with a random effects model. Results: Among 733 identified articles, 23 met inclusion criteria. Of the 883 included patients, 203 were managed medically (23%), 300 conservatively (34%) and 380 surgically (43%). Conservative patients had more extracranial complications (ECC, P = 0.04) and intratemporal complications (IT, P = 0.04) at follow-up compared with medical patients. Medical patients had more total number of complications (TNC, P = 0.03), ECC ( P = 0.02), and IT ( P = 0.01) at discharge compared with surgical patients. Conservative patients had more of all complications except intracranial/extracranial abscess and "other" at discharge and follow-up compared with surgical patients. Conclusions: There were larger reductions in TNC, ECC, and IT at discharge and follow-up among surgical patients compared with medical and conservative patients. There were greater reductions in TNC, ECC, IT, intracranial complications, subperiosteal abscess and lateral sinus thrombosis at discharge and follow-up among surgical patients compared with conservative patients.